Teologi Menstruasi: Antara Mitologi dan Kitab Suci - Umar, Nasaruddin (Musawa Jurnal Studi Gender dan Islam, 2007)
Menstruation - called haid in Islamic fiqh, is not seen as merely physical, biological function of women's bodies. According to most traditional societies, this very exclusive women's experience is apparently perceived to be a symbol signifying specific meaning and myth. Unsurprisingly almost all societies have conceptualized what so called menstrual taboo in an anthropological tradition within their cultural systems. One of the major implications of these ideas of menstrual taboos is the emergence of devices signifying the event of menstruation, such as cosmetics, high heel footwear, and jilbab. Another significant impact is the restriction of women's social role and engagement. This article is addressing these two mythical and social implications of menstrual taboos and compare them with Islamic doctrines of haid.